Internalisasi Nilai-Nilai Pendidikan Islam KH. Hasyim Asy’ari Dalam Film Sang Kiai - Sa’atun Zohria; Abdul Jalil; Achmad Subekti (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
The shifting of the meaning of education into teaching is only very influential for students and educators. Learners experience an intcrease in cognitive values but not affective aspects and educators carry out their pask regardlass of whether they succeed in transferring values to students. The kiai’s films are verymuch in accordance with emergence of the above thoughts, in the film the cribed the journey of a gread religious figure who embodies the value of sincerity as will as being example of his sabtrinya. The pourpose of the study wes to formulate a problem regarding the internalization of Islam KH. Hasyim Asy’ari in the kiai’s films and the implemantation of the value of education in modern times. To achieve this goal the researcher uset qualitative methods with a type of historical study and collected data using observation and documentation methogs. From the results of this study, it can be concluded that there are six values of islamic education in the film of the Kiai an the way that kh. Hasyim Asy’ari is very creative in stilling the value of education that can be implemented in the world of modern education.